If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 + -2i = 3 + -3i Solving 4 + -2i = 3 + -3i Solving for variable 'i'. Move all terms containing i to the left, all other terms to the right. Add '3i' to each side of the equation. 4 + -2i + 3i = 3 + -3i + 3i Combine like terms: -2i + 3i = 1i 4 + 1i = 3 + -3i + 3i Combine like terms: -3i + 3i = 0 4 + 1i = 3 + 0 4 + 1i = 3 Add '-4' to each side of the equation. 4 + -4 + 1i = 3 + -4 Combine like terms: 4 + -4 = 0 0 + 1i = 3 + -4 1i = 3 + -4 Combine like terms: 3 + -4 = -1 1i = -1 Divide each side by '1'. i = -1 Simplifying i = -1
| 2a-8=-9+7 | | U-8.49=4.1 | | 4-21=3-31 | | -9r-5r=34 | | 4k+20=-2k+8 | | 12n+1n=3 | | 4=w/15 | | -x-13=7+4x | | 1/2n+16=4-2/3 | | 4x+13=nx+13 | | 6n=5x+2 | | (2x^2+14x+24)/(x+5) | | 18-n=5n | | V-6.22=8.96 | | 2+7x=32+32 | | d=2(46)2 | | =18-(3-10g) | | 2(4-3t)-(-3)+2= | | ((x/4)+(4*x))/(x/7)=56.7 | | T/45+2/11=-4/11 | | sqrt(363ab^5c^7)= | | 16=d-12/4 | | 2(3x-10)=4 | | 6x+21=16x-51 | | 4x+9=18- | | 3x-2+22=40 | | 4w^2=-9w-2 | | -2(-z+8)+3z=29 | | -(x-5)=m(4-5x) | | 129+.25x=216.50 | | 5x-20=85 | | 6+6x=20+2x |